L Laga Pinter as A Learning Media in The Material Rectangle of Student Class VII K SMP Negeri 5 Kendari - Asri Azis (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
The purpose of this research is the use of